2013
DOI: 10.1515/znc-2013-7-804
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Variegated Pink-Fleshed Lemon (Citrus x limon L. Burm. f.) and their Anti-Inflammatory and Antimicrobial Activities

Abstract: The volatile secondary metabolites of essential oils from fruit peel and leaves of variegated pink-fl eshed lemon (Citrus x limon) were investigated using GLC and GLC-MS (gas-liquid chromatography-mass spectroscopy). Altogether 141 compounds were identifi ed and quantifi ed, accounting for 99.59% and 96.33% of the total hydrodistilled peel and leaf oil, respectively. Limonene occurred in higher amounts in fruit peel (52.73%) than in leaf oil (29.13%). Neral (12.72%), neryl acetate (8.53%), ρ-menth-1-en-7-al (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The study found evidence that IL-6 markedly decreased during dietary supplementation with D-limonene [51]. Another study showed that the oil moderately inhibited soybean 5-lipoxygenase (5-LOX) with an IC 50 value of 32.05 µg/mL (Table 8) [52].…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
See 3 more Smart Citations
“…The study found evidence that IL-6 markedly decreased during dietary supplementation with D-limonene [51]. Another study showed that the oil moderately inhibited soybean 5-lipoxygenase (5-LOX) with an IC 50 value of 32.05 µg/mL (Table 8) [52].…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
“…Moreover, under another study, C. limon essential oil showed antibacterial activity against Gram-positive bacteria (Bacillus subtilis (MIC 2 mg/mL), Staphylococcus capitis (MIC 4 mg/mL), Micrococcus luteus (MIC 4 mg/mL)), and Gram-negative (Pseudomonas fluorescens (MIC 4 mg/mL), Escherichia coli (100% inhibition)) ( Table 8) [52,53].…”
Section: Antimicrobial Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…Nordihydroguaiaretic acid (NDGA) was used as a positive control (IC 50 = 0.24 lg/ ml). [26] In vivo assessment (Rat paw oedema assay)…”
Section: -Lipoxygenase Inhibitionmentioning
confidence: 99%